1985
DOI: 10.1111/j.1365-2125.1985.tb05100.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against an acetylcholine releasing action of cisapride in the human colon.

Abstract: The effect of cisapride (R51619) on intrinsic cholinergic nerve activity of human sigmoid taenia coli muscle strips (taeniae) was assessed using radiolabelling techniques. Taeniae previously incubated with [3H]-choline were exposed to cisapride (0.41 and 4.1 ,uM), placebo solution and electrical field stimulation (EFS; 10 Hz, 1 ms, 200 mA for 480 pulses). Cisapride did not affect unstimulated (basal) release of radioactive material nor the release evoked by EFS. It was concluded that cisapride did not demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Our study thus shows that in human colon, excitatory 5-HT 4 receptors are present on cholinergic nerves within the CM layer, similar to those shown before on the cholinergic nerves within the longitudinal muscle layer. 9 The non-effect of cisapride on electrically induced acetylcholine release in human colonic taenial longitudinal muscle reported earlier 16 is probably due to the partial agonist effect of cisapride on 5-HT 4 receptors being insufficient to enhance acetylcholine release from cholinergic nerves. The presence of excitatory 5-HT 4 receptors on cholinergic nerve endings in human colon CM, and longitudinal muscle 9 contrasts with findings in longitudinally mounted guinea-pig colon segments, suggesting that 5-HT 4 receptors are primarily located on the soma of intrinsic motor neurones.…”
Section: Discussionmentioning
confidence: 93%
“…Our study thus shows that in human colon, excitatory 5-HT 4 receptors are present on cholinergic nerves within the CM layer, similar to those shown before on the cholinergic nerves within the longitudinal muscle layer. 9 The non-effect of cisapride on electrically induced acetylcholine release in human colonic taenial longitudinal muscle reported earlier 16 is probably due to the partial agonist effect of cisapride on 5-HT 4 receptors being insufficient to enhance acetylcholine release from cholinergic nerves. The presence of excitatory 5-HT 4 receptors on cholinergic nerve endings in human colon CM, and longitudinal muscle 9 contrasts with findings in longitudinally mounted guinea-pig colon segments, suggesting that 5-HT 4 receptors are primarily located on the soma of intrinsic motor neurones.…”
Section: Discussionmentioning
confidence: 93%
“…It was even suggested that a 5-HT 4 receptor-mediated mechanism of release of acetylcholine was absent in the human colon, on basis of the observation that the 5-HT 4 receptor agonist cisapride failed to modify unstimulated or EFS-stimulated release of 3 H-acetylcholine from human colonic taenial muscle (Burleigh & Trout, 1985). Interestingly, the endogenous ligand 5-HT was not tested in that study.…”
Section: Discussionmentioning
confidence: 94%
“…41 Prokinesia may result from increased release of acetylcholine (and tachykinins) from excitatory neurones and may operate in human small bowel and stomach, 103 104 but early investigations failed to identify this pathway in human colonic circular muscle. 105 An in vivo study in dogs showed that tachykininergic pathways play an important role in mediating the colonic motor response to administration of the 5-HT 4 receptor agonist ML10302 whereas they are not involved in ML10302 induced prokinesia in the small bowel. 106 Besides these actions, 5-HT 4 receptors also affect secretory processes at the mucosal level.…”
Section: -Ht 3 Receptor Agonists In Therapeutics: Preliminary Evidencementioning
confidence: 99%